Pengaruh Promosi Kesehatan Mengenai Covid-19 terhadap Kualitas Hidup Masyarakat - M Dana Prihadi; Chicy Indah Sari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
COVID-19 is a new disease that causes infection in the human respiratory tract and has a fairly high transmission rate. The problem related to this disease is the lack of public awareness in implementing a healthy lifestyle for the prevention and transmission of COVID-19. One way to gain knowledge and insight regarding the application of a healthy lifestyle is to organize health promotion through visual media and print media that are distributed to patients in the Cibogo Community Health Center, Subang Regency. Health promotion that is intensified through visual media and print media is expected to encourage people to capture, understand and remember the messages conveyed in the media, so that lifestyles can change according to science. This study uses a quantitative approach in which the calculation results will be described descriptively. There were 94 questionnaires distributed, each of which consisted of 13 statements. Based on research findings, health promotion through digital media attracts more public attention through print media. In addition, quality of life, in this study, is public awareness in implementing health protocols and implementing them in daily life.